2018
DOI: 10.1080/13561820.2018.1515191
|View full text |Cite
|
Sign up to set email alerts
|

Variables associated with interprofessional collaboration: The case of professionals working in Quebec local mental health service networks

Abstract: This study identified variables associated with interprofessional collaboration (IPC) among 315 mental health (MH) professionals working in primary health care (PHC) and specialized teams, within four Quebec (Canada) local service networks (LSNs). IPC was measured with a validated scale, and independent variables were organized according to a four-block conceptual framework that included Individual, Interactional, Organizational and Professional Role Characteristics. Bivariate and multiple linear regression an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 67 publications
1
8
0
Order By: Relevance
“…The results of this study demonstrate the strong correlation between interprofessional collaboration and teamwork climate in all dimensions of both instruments used, reinforcing the importance of assessing teamwork climate in health services to promote more comprehensive, resolutive and higher-quality health care. This correlation was also observed by Ndibu et al (2019) 18 and suggested by Agreli, Peduzzi and Bailey (2017) 12 in a study of mixed methods, in which the team climate seemed to be related to some aspects of interprofessional collaboration.…”
Section: Discussionsupporting
confidence: 79%
“…The results of this study demonstrate the strong correlation between interprofessional collaboration and teamwork climate in all dimensions of both instruments used, reinforcing the importance of assessing teamwork climate in health services to promote more comprehensive, resolutive and higher-quality health care. This correlation was also observed by Ndibu et al (2019) 18 and suggested by Agreli, Peduzzi and Bailey (2017) 12 in a study of mixed methods, in which the team climate seemed to be related to some aspects of interprofessional collaboration.…”
Section: Discussionsupporting
confidence: 79%
“…Studies with teams of mental health professionals demonstrate that collaborative practice is limited without the participation of an expert in each field [ 2 ], which is an aspect that our study indicates as fundamental for the scaling of this type of learning. We consider that the professional characteristics of each role is what should be prepared and simulated in order to be positioned in a team before simulating the team in clinical care, at least in this stage of training.…”
Section: Discussionmentioning
confidence: 95%
“…Students of both nursing and psychology have historically participated in clinical learning activities often referred to as practica, which involve the observation of an experienced professional while performing activities directly with patients, depending on the skills of their clinical facilitators [ 1 , 2 ]. Practica have interactive features that create opportunities for students to experience working in a clinical setting within a team.…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, future adaptations of the IP-SDM model may benefit from implementing behavior change techniques specifically targeting social influence. In a separate study with interprofessional teams within a Quebec mental health network, strategies such as providing information about peer approval, promoting trust through social comparison, and fostering social support/change emerged as relevant approaches that could be integrated in future adaptations [ 29 , 30 ]. Moreover, we found a statistically significant association between beliefs about capabilities and intention.…”
Section: Discussionmentioning
confidence: 99%